Epidemiological Study of Microfilariasis in Three Different Geographical Regions of Nepal - Manandhar, R (2016)
Background: Bancroftian filariasis is spreading as an endemic in many parts of Nepal and is a major public health problem. This paper deals with the prevalence of micrifilaraemia and filarial disease studying their association with individual characteristics and variables related to exposure to the vectors. Methods: The survey was conducted in Bhaktapur, Palpa and Bhairahawa covering three different geographical regions between January 2001-November 2001. Microfilaria was examined by multiple diagnostic techniques using blood collected between 20.00-01.00 as well as ICT card method. The male/female aged between 20 and 65 years were interviewed with questionnaire. Results: The risk of being microfilaria was greater among those who had lived in the study area for more than 15 years. The disease prevalence was 0.31%. The chronic clinical manifestation was found in both male and female and was increased with age. The cases of hydrocele in male were noticed more in terai and inner terai but microfilaraemic cases detected in hill. The survey showed that smear from buffy coat of night blood was the best to find microfilaria. ICT card method was found very satisfactory for diagnosis of antigenemia in Wuchereria bancrofti infection. Conclusions: Detection of parasite from microfilaraemia cases was found low compared with the laboratory diagnosis of antigenemia in Wuchereria bancrofti infection. In Bhaktapur district many cases of leg encephalitis were observed. Hydrocele cases were found more in terai and inner terai area but microfilaria was not detected from the urine specimens. Keywords: filariasis; hydrocele; microfilaraemia; prevalence.